Analysis Of Land Value Zone Changes Due To The Construction Of The Kediri International Airport In Grogol Sub-District, Kediri Regency - Amarrohman, Fauzi Janu; Qoyimah, Shofiyatul; Fatihulhaq, Muhammad Aidil (Journal of Applied Geospatial Information, 2024)
Grogol Sub-district is one of the areas in the administration of Kediri district. Kediri District continues to carry out development, one of which is the Kediri International Airport Development. The development of Kediri International Airport in the Grogol District area began from 2019 until 2023. The research data used the 2016 Land Value Zone Map data of 17 zones, in 2019 with 20 zones, and in 2023 with 20 zones. The method used is the overlay method analysis to find out how many land value changes occur. The analysis method uses a regression test to determine the effect of airports and provincial roads on the land value zone (ZNT). During the period 2016 to 2023, the results of data processing showed the development of land value zones in 20 zones. Between 2016 and 2019, there was an increase in the Average Indicated Value (NIR) in the Cerme Village area in zone number 528 of Rp. 125,000 with a percentage of 78.13%. Conversely, in the Datengan Village area, zone 395 experienced a drastic decrease of -95% or IDR -114,000 due to zone restructuring and distance from the airport. Between 2019 and 2023, Grogol Village in zone 568 recorded the highest increase in NIR of IDR 1,013,876, with a percentage of 221.85%. Meanwhile, zone 395 again emerged with an increase in NIR of Rp. 5,274 or 4.4%. The results showed the influence of airports and provincial roads on ZNT changes in 2016 - 2023 with an R Square value of 0.385 or has an impact value of 38.5% with a negative correlation where the closer the zone is to the airport, the higher the NIR value, on the other hand, the farther the zone is, the smaller the NIR value.